Pannexin‐2 is expressed in the human colon with extensive localization in the enteric nervous system. Issue 5 (14th March 2015) - Diezmos, E. F.; Sandow, S. L.; Perera, D. S.; King, D. W.; Bertrand, P. P.; Liu, L.
Abstract: Background: Pannexin‐2 (Panx2) is a member of the novel group of membrane spanning protein channels present in the central nervous system. Limited studies have examined Panx2 in the intestine, where it may have important physiological roles. The present study characterized Panx2 expression and localization in the human colon in health and disease states. Methods: Immunofluorescence determined Panx2 localization and co‐localization, and quantitative real‐time PCR and Western blot determined gene and protein expression in ulcerative colitis (UC), Crohn's disease (CD), and control human colon. Key Results: Panx2 was widely expressed in myenteric and submucosal ganglia, particularly in the cytoplasm of neurons. Panx2 was also expressed on smooth muscle of the muscularis and blood vessels, some non‐lymphoid leukocytes, mast cells, and mucosal epithelial cells. Co‐localization of Panx2 occurred with β ‐tubulin, neuronal nitric oxide synthase, substance P, vesicular acetylcholine transporter, and calcitonin gene‐related peptide, indicating widespread Panx2 expression in extrinsic and intrinsic neurons. Molecular studies revealed a 3.4‐fold higher level of Panx2 mRNA in ascending compared to sigmoid muscularis ( p  < 0.05), despite similar protein levels. Similarly, UC muscularis showed a 35‐fold up‐regulation in Panx2 mRNA, but not in protein ( p  < 0.05). Conclusions & Inferences: Here, we demonstrated the dense expression of Panx2 in the enteric nervous system and the co‐localization of Panx2 with a spectrum of neuronal markers, indicating that Panx2 may be involved in mediating neurotransmission in the colon. The substantial increase in Panx2 mRNA in UC muscle but not protein suggests that the Panx2 translation process may be disrupted in UC. Abstract : The goal of this study was to determine the localization of Panx2 in the human colon, and to investigate gene and protein expression levels in inflammatory bowel diseases (IBD). By using immunohistochemistry, real‐time PCR and Western blot, we demonstrated that Panx2 was widely expressed in the enteric nervous system, co‐localizing with neuronal markers which indicate expression on motoneurons, interneurons, and neurons involved in nociception. Panx2 expression in ulcerative colitis was up‐regulated at the gene but not protein level, indicating that translation of Panx2 may have been disrupted in this disease.